Betulin-related esters from birch bark tar: Identification, origin and archaeological significance. (January 2020) - Perthuison, Julien; Schaeffer, Philippe; Debels, Pauline; Galant, Philippe; Adam, Pierre
Highlights: Betulin-related esters in archaeological samples were identified via synthesis. They are formed by reaction of suberin fatty acids and betulin-related triterpenoids. They are potential new biomarkers of strong heating upon tar preparation. Abstract: Birch bark tar, an organic material frequently encountered during archaeological excavations, has been identified from its lipid composition on the cracks of a ceramic dated to the late Neolithic. Lipids of this black substance were dominated by a characteristic triterpenoid assemblage of lupane-related triterpenoids from birch bark, together with their thermal degradation products formed during preparation of the tar. Among the latter, four main series of unusual triterpenoid esters have been detected and were postulated to correspond to esters of Δ 2 -betulin and Δ 2 -dihydrobetulin based on their mass spectra and hydrolysis experiments. Their conclusive identification has been achieved by synthesis of reference compounds. These compounds most likely originate from the esterification between triterpenoid alcohols related to betulin and fatty acids from suberin formed upon heating of birch bark tar. They could be considered as markers of intense heating during birch bark tar preparation using the "single pot" procedure.